2018
DOI: 10.1038/s41557-018-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Reversible calcium alloying enables a practical room-temperature rechargeable calcium-ion battery with a high discharge voltage

Abstract: Calcium-ion batteries (CIBs) are attractive candidates for energy storage because Ca has low polarization and a reduction potential (-2.87 V versus standard hydrogen electrode, SHE) close to that of Li (-3.04 V versus SHE), promising a wide voltage window for a full battery. However, their development is limited by difficulties such as the lack of proper cathode/anode materials for reversible Ca intercalation/de-intercalation, low working voltages (<2 V), low cycling stability, and especially poor room-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
434
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 1,448 publications
(450 citation statements)
references
References 26 publications
10
434
1
5
Order By: Relevance
“…[33] The calciation voltages corresponding to these phases declines from 0.99, 0.72, 0.59 to 0.53 V relative to Ca/Ca 2+ ( Figure 1B) while the volume expansion of the system per Ca accommodated increases from 7.4, 27.5, 27.6, 28.8 to 31.1 Å 3 ( Figure 1C). For instance, the experimental calciation of Sn ends at Ca 7 Sn 6 , [14] and the calculated calciation voltage of the Sn-Ca system ( Figure 1B) reaches a value of 0.53 V (relative to Ca/Ca 2+ ) for Ca 7 Sn 6 . For instance, the experimental calciation of Sn ends at Ca 7 Sn 6 , [14] and the calculated calciation voltage of the Sn-Ca system ( Figure 1B) reaches a value of 0.53 V (relative to Ca/Ca 2+ ) for Ca 7 Sn 6 .…”
Section: Sn-ca Phase Diagram and The Electrochemical Sn-ca Reactionsmentioning
confidence: 94%
See 4 more Smart Citations
“…[33] The calciation voltages corresponding to these phases declines from 0.99, 0.72, 0.59 to 0.53 V relative to Ca/Ca 2+ ( Figure 1B) while the volume expansion of the system per Ca accommodated increases from 7.4, 27.5, 27.6, 28.8 to 31.1 Å 3 ( Figure 1C). For instance, the experimental calciation of Sn ends at Ca 7 Sn 6 , [14] and the calculated calciation voltage of the Sn-Ca system ( Figure 1B) reaches a value of 0.53 V (relative to Ca/Ca 2+ ) for Ca 7 Sn 6 . For instance, the experimental calciation of Sn ends at Ca 7 Sn 6 , [14] and the calculated calciation voltage of the Sn-Ca system ( Figure 1B) reaches a value of 0.53 V (relative to Ca/Ca 2+ ) for Ca 7 Sn 6 .…”
Section: Sn-ca Phase Diagram and The Electrochemical Sn-ca Reactionsmentioning
confidence: 94%
“…[17] Alloying-type anodes, widely studied for Li-ion batteries, show great promise for reversible CIBs. Using a Sn anode and graphite cathode, Wang et al [14] recently reported a highvoltage (4.45 V) CIB cell with a reasonable capacity of 85 mAh g and a remarkable cyclability (95% capacity retention in 350 cycles). Besides Sn, several metals and metalloids including Zn, Al, Si, Li, and Na have also been investigated for the use of alloying-type CIBs anodes with largely disparate capacities achieved.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations